Performance of community health centres for providing non-communicable diseases services: non-communicable diseases clinics and context for actions - Rao, Gangadhar (International Journal Of Community Medicine And Public Health, 2022)
Background: The increasing burden of noncommunicable diseases (NCDs) has been seen as a significant development barrier in the twenty-first-century era. In 2016, nearly 4.1 crore mortalities happened due to noncommunicable diseases only, equivalent to 71% of the overall 5.7 crore deaths.Most of these mortalities were triggered by the four main NCDs, like cardiovascular disease, cancer, chronic respiratory disease and diabetes. These NCDs have become one of the significant health systems challenges in developing countries. Methods: The current study is a concurrent mixed methodological approach which gives equal weightage. Results: The study has identified nine significant domains from the qualitative part. The content analysis was used for quantitative approach which has found that nearly 89.6% feels services are available and 10.4% feels there are lacuna in services. The diseases distribution was diabetes 25.3%, cardiovascular diseases account for 30.9%, chronic respiratory account for 26.9%, cancer 3.9%, and multimorbidity accounts for 12.6%. From the content analysis, it is understood from the beneficiaries that whenever the healthcare professional is free, they are providing the promotive and preventive service, 59.5%. Conclusions: It was understood that the NCD clinics are functional. The NCD clinics are providing the basic services for majority of NCDs. Although the lacuna exists in the health systems with respect to human resources and other factors. There is increased utilization of services compared with past. The role efficacy was found to be high.